PENGARUH PENYAJIAN LAPORAN KEUANGAN, SISTEM PENGENDALIAN INTERNAL DAN AKSESIBILITAS LAPORAN KEUANGAN TERHADAP AKUNTABILITAS PENGELOLAAN KEUANGAN DAERAH ( Studi Empiris Pada OPD Pemerintah Kota Pematangsiantar) - Purba Menrokis; Agusti Restu; Rofika Rofika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to examine the effect of the presentation of financial statements, internal control systems and accessibility of financial reports on the accountability of regional financial management. The population of this research is 23 opd in Pematangsiantar city government. The sampling technique used in this research is purposive sampling. The data were processed using SPSS version 25 and analyzed using multiple linear regression analysis. The dependent variable in this study is the accountability of regional financial management. The independent variables used in this study are the presentation of financial statements, the internal control system and the accessibility of financial statements. The results of this study indicate that the presentation of financial statements affects the accountability of regional financial management at a significance level of 0.001 < 0.05, the internal control system affects the accountability of regional financial management at a significance level of 0.000 < 0.05, the accessibility of financial statements affects the accountability of regional financial management. at a significance level of 0.006 < 0.05.Keywords : the effect of financial statement presentation, internal control system, accessibility of financial reports and accountability of regional financial management.